2020
DOI: 10.4038/sljid.v10i1.8247
|View full text |Cite
|
Sign up to set email alerts
|

Farmers’ occupational health, perception and practices towards leptospirosis: A cause for concern

Abstract: This an open-access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 6 publications
1
8
0
Order By: Relevance
“…Even though health-seeking behaviour was assessed as subcomponents in different studies there were no proper knowledge scoring and categorization done. Yet Mathanamohan, et al, 2020 (7) in the study done among farmers in Colombo district concluded the sample had satisfactory knowledge of healthcare-seeking. The satisfactory knowledge score could be due to repeated educational activities carried out over last few years targeting high risk communities to enhance early health seeking targeting secondary prevention.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…Even though health-seeking behaviour was assessed as subcomponents in different studies there were no proper knowledge scoring and categorization done. Yet Mathanamohan, et al, 2020 (7) in the study done among farmers in Colombo district concluded the sample had satisfactory knowledge of healthcare-seeking. The satisfactory knowledge score could be due to repeated educational activities carried out over last few years targeting high risk communities to enhance early health seeking targeting secondary prevention.…”
Section: Discussionmentioning
confidence: 96%
“…Farmers who did not engage in farming for more than 2 years were excluded. Appropriate statistical methods for descriptive studies, was used to calculate the sample size where the existing prevalence of knowledge was taken from previous similar studies for the reference in Mathanamohan et al (2020) (7) in Colombo district and Samarakoon and Gunewardene (2013) (8) in Kurunegala district. The design factor, 1.3 was used to overcome the design effect of the cluster sampling and 5% non-response rate was considered to adjust the sample size to enhance the internal validity of the study, with the calculated nal sample of of 436 farmers.…”
Section: Methodsmentioning
confidence: 99%
“…There are various mutual factors related so that can cause individual infected with leptospirosis. So from That needed awareness and improvement education for farmer related to leptospirosis (Mathanamohan et al, 2020). Besides education prevention is also important education in inspection until treatment.…”
Section: Discussionmentioning
confidence: 99%
“…The nding of Guernier et al [21] indicates that farming activities could increase the burden of human leptospirosis, either individually or in combination with other factors, which shows that the study supports our ndings. Moreover, Mathanamohan et al [22] reported leptospirosis consequences and preventative measures to be occupationally connected to farming. Cross-sectional research conducted by Maze et al [23] indicated rice eld workers to be more predisposed to acute leptospirosis.…”
Section: Discussionmentioning
confidence: 99%